Deformation Behavior of Inconel 617 Alloy Under Monotonic and Cyclic Loading - Santhi Srinivas N.C.; Visweswara Rao C.; Sastry G.V.S.; Singh V. (My University, 2025)
Inconel 617 alloy is used in important power plant applications involving steam generation equipment such as boiler superheaters and reheaters. Deformation behavior of the IN 617 alloy under monotonic and cyclic loading at room temperature, 750 and 850 ℃ at strain rate of 0.005 s−1 was studied in the present investigation. Under tensile loading, decrease in strength was observed at 750 and 850 ℃ compared to the value observed at RT. Transmission electron microscopy (TEM) studies revealed traces of slip bands whereas precipitation of carbides and γ׳ at 750 and carbides at 850 ℃. Formation of slip bands suggests slip as the primary mechanism of deformation under tensile loading at RT. Continuous cyclic hardening under cyclic loading was observed, at all the three temperatures and at all the strain amplitudes. Cyclic hardening was noticed till peak hardening at 750 and 850 ℃ at all the strain amplitudes. Increase in temperature of testing had deleterious influence on fatigue life. Cyclic hardening at RT was attributed to, the existence of pile up of dislocations in planar array in slip bands, the interaction of dislocations with the fine carbide and γ׳ particles at 750 ℃ and with the carbides particles at 850 ℃. © 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.